Market conducts supervisory phenomenon in Indonesia - Anto Prabowo (Universitas Sebelas Maret, 2021)
Our study aims to contribute to the research literature in market conduct supervision as a global and fundamental component in financial consumer protection, especially the post-2008 Global Financial Crisis. The international regulatory institutions had agreed on the need for a robust framework for market conduct supervision. However, the actual implementation of market conduct supervision by the Indonesia Financial Services Authority is lacking behind other topics. General research articles of market conduct supervision in Indonesia rarely discuss the economic aspects of the phenomena, emphasizing the analysis of the legal dynamics of the phenomena. Therefore, using focus group discussion, literature review, and Social Fabric Matrix, we try to visualize the overall landscape of the market conduct supervision in Indonesia.